2006
DOI: 10.1007/s10047-006-0353-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric problems of heart transplant candidates with left ventricular assist devices

Abstract: Most heart transplant candidates are equipped with left ventricular assist devices (LVADs). LVAD therapy is associated with characteristic psychiatric and psychosocial problems. To investigate the mental states of heart transplant candidates, psychiatric diagnosis, psychological or behavioral problems, and the need for treatment were evaluated around the time of registration to the waiting list and during follow-up. Saitama Medical University Hospital has been designated a hospital for heart transplantation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Some studies found that only 2% of LVAD patients experienced depression and only 4% experienced anxiety, 20 whereas others found a considerable group of LVAD patients experiencing a depressive or adjustment disorder (21% and 37%-50%, respectively). 29,31 In trials (ie, the Randomized Evaluation of Mechanical Assistance in the Treatment of Congestive Heart Failure trial) comparing LVAD patients using pulsatile devices with patients using optimal medical treatment and transplant recipients, LVAD support was associated with a significant improvement in health status and depressive symptoms in contrast to medication alone (PϽ0.05 for both). 26,30,32 However, LVAD patients do not seem to attain the same level of health status compared with transplant recipients, with transplant recipients experiencing more improvements in mobility, self-care ability, physical ability, and social functioning than LVAD patients.…”
Section: Brouwers Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found that only 2% of LVAD patients experienced depression and only 4% experienced anxiety, 20 whereas others found a considerable group of LVAD patients experiencing a depressive or adjustment disorder (21% and 37%-50%, respectively). 29,31 In trials (ie, the Randomized Evaluation of Mechanical Assistance in the Treatment of Congestive Heart Failure trial) comparing LVAD patients using pulsatile devices with patients using optimal medical treatment and transplant recipients, LVAD support was associated with a significant improvement in health status and depressive symptoms in contrast to medication alone (PϽ0.05 for both). 26,30,32 However, LVAD patients do not seem to attain the same level of health status compared with transplant recipients, with transplant recipients experiencing more improvements in mobility, self-care ability, physical ability, and social functioning than LVAD patients.…”
Section: Brouwers Et Almentioning
confidence: 99%
“…Patients supported by pulsatile devices showed relatively high mean depression scores just after LVAD implantation. 26,29,31 The retrospective study 19 of Bunzel et al 20 found no significant difference in depression scores between patients receiving therapy via pulsatile vs continuous-flow devices; these patients might be more vulnerable to psychological distress, based on the higher rate of complications and the characteristics of the device (eg, short durability, large size, noise, and large batteries). Hence, these differences in findings could well be explained by sample size limitations, differences in subtype of devices, and the time of collecting data.…”
Section: Summary Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study [29] reported the following complications: 14% recovered after CVA, 14% died from CVA, 21% became infected, and 21% experienced delirium. Psychiatric diagnoses by DSMIV criteria included adjustment reaction in 50%, of patients, delirium in 21%, depression NOS in 14%, major depression (MDD) in 7%, brief psychosis in 7%, and dissociative disorder in 7%.…”
Section: Medical and Neuropsychological Complications After Lvadmentioning
confidence: 96%
“…Because patients using VAS are prone to depression, anxiety, feelings of irritation, and fear of death, a team of cardiologists, nurses, psychiatrists, clinical psychotherapists, and psychiatric liaison nurses should offer mental support. 63 Family members of patients using VAS need practical support to reduce the burden of patient care as well as mental support.…”
Section: Nursing In the Initial Assessment Of Acute Heart Failurementioning
confidence: 99%